Оптимізація організації інтернатури за фахом «Дитяча анестезіологія» в заочному періоді навчання - Курочкін, Михайло Юрійович; Kurochkin, M. Yu.; Курочкин, М. Ю. (ВДНЗ «Українська медична стоматологічна академія», 2015)
Сучасна інтернатура за фахом «дитяча анестезіологія» - завершальний етап підготовки лікарів перед початком їх самостійної практичної діяльності. Виховання лікарської майстерності залежить від організації методики викладання та координації навчання на очному та заочному етапах. Нами створено комплексний підхід в організації учбового процесу на заочних базах навчання з елементами дистанційного навчання (на базі платформи Moodle). Самостійна робота під керівництвом досвідченого фахівця на заочній базі навчання дозволить оволодіти лікарям-інтернам алгоритмами надання невідкладної допомоги при ургентних ситуаціях в педіатрії, сприятиме розвитку практичної досконалості, дасть змогу самостійно знаходити знання, засвоювати їх, ефективно використовувати та обновляти. Виконання вищезазначених умов буде сприяти формуванню найважливішої складової лікарської майстерності - клінічного мислення. Современная интернатура по специальности «детская анестезиология» - завершающий этап подготовки врачей перед началом их самостоятельной практической деятельности. Воспитание врачебного мастерства зависит от организации методики преподавания и координации обучения на очном и заочном этапах. Нами создан комплексный подход в организации учебного процесса на заочных базах обучения с элементами дистанционного обучения (на базе платформы Moodle). Самостоятельная работа под руководством опытного специалиста на заочной базе обучения позволит овладеть врачам-интернам алгоритмами оказания неотложной помощи при ургентных ситуациях в педиатрии, будет способствовать развитию практического совершенства, позволит самостоятельно находить знания, усваивать их, эффективно использо¬вать и обновлять. Выполнение вышеупомянутых условий будет способствовать формированию важнейшей составляющей врачебного мастерства - клинического мышления. Modern internship in specialty “pediatric anesthesiology” is the final stage of doctor’s preparation. The internship is designed to theoretical and practical training on many important professional issues that medical interns receive under the guidance of university professors and heads of distance-learning-based for the entire period of study internship. The aim. To optimize the training of interns in “pediatric anesthesiology” and to create conditions for its transformation into a high school clinical skills. The main part. The programme of the internship in “pediatric anesthesiology” is divided into two periods - intramural and e x tramural, and at each of these periods medical interns have heads of their work. It is necessary to choose the base of probation of future doctor, it must have medical diagnostic departments, operating with modern equipment, laboratories and diagnostic studies, to be provided with modern medical equipment. Also, hospitals must have training facilities for interns, equipped with necessary teaching aids, tables, models, stand, modern technologies. Training in the organization of work on the bases of absentia education should be carried out in May - June. The preparation includes the certification of base of absentia education, check orders governing the work of the heads of the interns at the bases of absentia education for the ne x t academic year; orders of the distribution of interns in training bases, planning the organization of training of interns in the absence of relevant departments on the bases of practical training. To discuss these and other issues, we propose to hold a meeting in May for the staff of the faculty if postgraduate education, heads of interns and deputies chief of the hospital. The participation of the latter is very reasonable for a more effective interaction between the department and databases practice in dealing with organizational issues. Training of interns depends on several factors - the capacity of clinical base of absentia education, personality of the head of interns, his qualifications, pedagogical skills, but is determined primarily motivated medical interns to gain knowledge, the level of its basic vocational education, are important psychological climate in the team, giving him a degree of autonomy in decision-making and in the implementation of manipulation. An independent work under the guidance of an e x perienced specialist in the clinic or on the basis of absentia education (alternating, curation of patients under the supervision of attending physician, participated in the e x amination of patients, perfoming the general anesthesia of varying difficulty, various methods of e x tracorporeal detoxification - discrete plasmapheresis, hemodialysis) helps to acquire medical algorithms, provide emergency assistance in urgent situations in pediatrics, will contribute to the development of practical e x cellence in clinical and instrumental e x amination of the patient, will determine the need for self-analysis, generalization, systematization, and inculcation of interns desire for self-education, the ability to find knowledge, assimilate them and to effectively use. Implementation of all of these conditions will favor the most important component of medical skill - clinical thinking. Conclusions. Thus, the physician’s skilsl are not just the sum of professional knowledge, its components are much more complicated. Optimising of the internship in «pediatric anesthesiology» in absentia period should help to form clinical skills.
Оптимизация организации интернатуры по специальности «Детская анестезиология» в заочном периоде обучения
Optimization of internship in the specialty «Pediatric Anesthesiology» in absentia period of education
Keywords: дитяча анестезіологія; лікарі-інтерни; оптимізація навчання; optimization of education; interns; pediatric anesthesiology; оптимизация образования; врачи-интерны; детская анестезиология